2016
DOI: 10.1177/1362361316646559
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in children and adolescents with autism spectrum disorder: A systematic review

Abstract: Despite limited evidence, complementary and alternative medicine treatments are popular in autism spectrum disorder. The aim of this review was to summarize the available evidence on complementary and alternative medicine use frequency in autism spectrum disorder. A systematic search of three electronic databases was performed. All research studies in English or German reporting data on the frequency of complementary and alternative medicine use in individuals with autism spectrum disorder were included. Two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 57 publications
(309 reference statements)
5
51
1
3
Order By: Relevance
“…Primary care providers are often asked about nonstandard interventions that are used in integrative practice or are promoted on the Internet, in the popular press, by other families, and by celebrities. [511][512][513][514][515][516] The National Center for Complementary and Integrative Health maintains a Web site in which current information on novel therapies in popular use for people with ASD is reviewed. 517 In the past decade, an increasing number of interventions based on theories of causation of ASD that are, as yet, unproven have been examined in clinical trials.…”
Section: Areas Of Psychopharmacologic Researchmentioning
confidence: 99%
“…Primary care providers are often asked about nonstandard interventions that are used in integrative practice or are promoted on the Internet, in the popular press, by other families, and by celebrities. [511][512][513][514][515][516] The National Center for Complementary and Integrative Health maintains a Web site in which current information on novel therapies in popular use for people with ASD is reviewed. 517 In the past decade, an increasing number of interventions based on theories of causation of ASD that are, as yet, unproven have been examined in clinical trials.…”
Section: Areas Of Psychopharmacologic Researchmentioning
confidence: 99%
“…Одним зі способів боротьби з системним запаленням, викликаним синдромом підвищеної кишкової проникності при багатьох захворюваннях, включаючи хвороби нервової системи, є безглютенова дієта, що не містить казеїну [41]. Існують припущення про патогенетичну роль молочних глютену і казеїну в розвитку шизофренії [16,29]. Ці припущення базуються на тому, що вказані інгредієнти призводять до надмірного накопичення екзорфінів у лікворі, що клінічно може проявитись симптомами шизофренії, аутизму.…”
Section: розлади аутистичного спектра і харчуванняunclassified
“…15,18 Stimulants are the most commonly used psychotropic medication. 17,18 Estimates of CHA use vary widely for children with ASD, ranging from 28% 19 to 95% 20 (median = 54%), 21 with special diets and supplements being the most frequently used CHA. 21 Children with ASD may use multiple services 17,19,22 ; however, little research has identified service use patterns and related characteristics among children with ASD.…”
mentioning
confidence: 99%
“…17,18 Estimates of CHA use vary widely for children with ASD, ranging from 28% 19 to 95% 20 (median = 54%), 21 with special diets and supplements being the most frequently used CHA. 21 Children with ASD may use multiple services 17,19,22 ; however, little research has identified service use patterns and related characteristics among children with ASD. Rather, past research has been focused on specific services used (eg, psychotropic medication), [14][15][16][17][18][19]23,24 the number of services, 17 weekly service hours, 14,25,26 and/or certain combinations of services used (eg, behavioral intervention and schoolbased therapy).…”
mentioning
confidence: 99%